Chameleon retail: environment responsive retail in the emerging market - Matondo, Florence S. (My University, 2015)
Commercial development within the emerging economy needs to simulate, adapt and respond accordingly to its unique environment. By doing so, a mutually beneficial relationship between the different scales of commerce, the community and their host environment is achieved. This thesis will focus on the retail aspect of what is later defined as the vibrant economic node. It will identify the current issues that exist within the community’s retail mode, thereafter, examining the various commercial proposals in similar types of communities. By investigating the area of a proposed development and establishing the status quo and providing the development with information of the brief for the project, this will, in turn, lead to a proposed solution that is more beneficial to the community. Investigations into cost effective and appropriate technologies that not only benefit the development but also provide an alternative solution to the community’s needs are investigated. A design proposal that embodies the ideals of what is defined as an environmental responsive commercial development, is brought forward as a demonstration of how a particular element within a framework can be beneficial.
Keywords: City planning; Retail trade; Commercial real estate; South Africa; Community development